Contre la métropole créative ... tout contre. Les politiques patrimoniales et touristiques de Plaine Commune, Seine-Saint-Denis - Saskia Cousin; Géraldine Djament-Tran; Maria Gravari-Barbas; Sébastien Jacquot (Métropoles)
This article questions the development of alternative policies, from the perspective of the political uses of tourism and heritage in Plaine Commune - one of the last territories of the red (communist) suburbs of Paris. The tourist and heritage policies are historically linked to the construction of a communist alternative and are marked by a militant perspective. These policies have evolved since the entrepreneurial turn initiated by the communist reformers in the 1990s. Today they are marked by the disseminating paradigm of "creativity". The involvment of the intermunicipal structure as "Territory of Culture and Creation" within the Greater Paris reveals the ambiguities between entrepreneurial dynamics and the development of a typical suburban heritage. In the interstices of the "creative" metropolis, we study the construction of alternative tourism and heritage policies. These policies are characterized by their participatory dimension, their involvment within the social and solidarity economy and their construction for ideally all inhabitants. In conclusion, the categorization of policies as alternatives stumbles on ambivalent forms, while the heritage and tourism policy, firsta result of an alternative policy, has become one of its main vectors.